New Exact Solutions of Some Important Nonlinear Fractional Partial Differential Equations with Beta Derivative - Ozkan, Erdogan Mehmet (MDPI, 2022)
In this work, the F-expansion method is used to find exact solutions of the space-time fractional modified Benjamin Bona Mahony equation and the nonlinear time fractional Schrodinger equation with beta derivative. One of the most efficient and significant methods for obtaining new exact solutions to nonlinear equations is this method. With the aid of Maple, more exact solutions defined by the Jacobi elliptic function are obtained. Hyperbolic function solutions and some exact solutions expressed by trigonometric functions are gained in the case of m modulus 1 and 0 limits of the Jacobi elliptic function.
Keywords: Benjamin Bona Mahony equation; Schrodinger equation; F-expansion method; Jacobi elliptic functions; beta derivative; DIFFUSION; Mathematics